Combining high time and angular resolutions: time‐resolved X‐ray powder diffraction using a multi‐channel analyser detector. (1st June 2015) - Choe, Hyeokmin; Gorfman, Semën; Hinterstein, Manuel; Ziolkowski, Michael; Knapp, Michael; Heidbrink, Stefan; Vogt, Marco; Bednarcik, Jozef; Berghäuser, Andreas; Ehrenberg, Helmut; Pietsch, Ullrich
<x xml:space="preserve">Abstract</x> The design and testing of the new MAD‐STROBO data acquisition system are reported. The system realizes stroboscopic collection of high‐resolution X‐ray powder diffraction profiles under a dynamically applied electric field. It synchronizes an externally applied stimulus and detected X‐ray photons. The feasibility of detecting sub‐millidegree shifts of powder diffraction profiles with microsecond time resolution is demonstrated. MAD‐STROBO may be applied for the investigation of various macroscopic and domain‐related processes induced by an external perturbation, such as elasticity or piezoelectricity.